2022
DOI: 10.3390/ijerph192417094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Digital Economy on PM2.5: Experience from the Middle and Lower Reaches of the Yellow River Basin

Abstract: The development of the digital economy holds great significance for alleviating haze pollution. To estimate the impact of the digital economy on haze pollution, this paper explores the spatiotemporal evolutionary characteristics of the digital economy and PM2.5 concentration in the middle and lower reaches of the Yellow River Basin from 2011 to 2019 and conducts regression analysis by combining a fixed effect (FE) model and the spatial Durbin model (SDM). Moreover, this study divides the mitigation effect of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The average annual precipitation and temperature are 636 mm and 15 °C, respectively, and this area is rich in biological resources, with nearly 800 and 60 kinds of plants and animals, respectively. The economic development of the region is dominated by traditional industries, such as the chemical and energy industries, and crop cultivation, which have a significant impact on the ecological environment of the lower Yellow River [ 57 ]. Cultivated land is widely distributed in this area, and the soil is mainly loam, clay, and silt.…”
Section: Methodsmentioning
confidence: 99%
“…The average annual precipitation and temperature are 636 mm and 15 °C, respectively, and this area is rich in biological resources, with nearly 800 and 60 kinds of plants and animals, respectively. The economic development of the region is dominated by traditional industries, such as the chemical and energy industries, and crop cultivation, which have a significant impact on the ecological environment of the lower Yellow River [ 57 ]. Cultivated land is widely distributed in this area, and the soil is mainly loam, clay, and silt.…”
Section: Methodsmentioning
confidence: 99%
“…These advancements are closely associated with green, low-carbon development, playing a crucial role in pollution mitigation. Numerous studies [30][31][32] have highlighted the digital economy's role in fostering the development of cleaner technologies and greener products. This is facilitated through the promotion of scientific and technological innovations, especially patents in green technology.…”
Section: Hypothesesmentioning
confidence: 99%
“…Recent studies have indicated that the development of the digital economy significantly impacts the reduction in PM 2.5 pollution [27]. The influence of the digital economy on PM 2.5 is primarily mediated through key factors, such as urban quality development and land use planning [28][29][30][31][32]. The exact manner in which the digital economy affects PM 2.5 pollution is not yet fully understood, necessitating further research to elucidate its mechanisms comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on their spatiotemporal evolution and correlation are also abundant, covering the scales of nations [29], urban agglomerations [30,31], climate zoning [32], provinces [33], and cities [34]. In terms of factors, the main focus is on natural factors-ranging from precipitation [35], vegetation [36], wind speed [37], and per capita GDP [30] to urbanization [38], digital economy [39,40], and other socio-economic factors-to analyze their effects on air pollutant concentrations. The specific factor research methods include GWR [41], machine learning [23,42], GeoDetector [43], and spatial metrics [44].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, this large river basin is one of the regions most strongly influenced by the relationship between humans and land. Due to the particularity of its natural environment and geographical location, the ecological environment of the YRB is always facing great threats [40]. Secondly, the YRB is a national strategic implementation region.…”
Section: Introductionmentioning
confidence: 99%